2013
DOI: 10.5402/2013/958461
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuronal Apoptosis in Volumetric Change of Hippocampus in Diabetes Mellitus Type 1: A Predictive Model

Abstract: Background. Neuronal apoptosis is the major cause of diabetes central neuropathy, but its role in volumetric changes of hippocampus has not been clarified. The aims of this study were to assess the role of apoptosis in volumetric changes of dentate gyrus (DG) and CA3 region of hippocampus and to determine a reference point in which these neuropathological changes reach a meaningful level. Methods and Materials. Diabetes was induced in male Wistar rats (N = 10) by streptozotocin (60 mg/kg). Six weeks after diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Long-term diabetes has been shown to cause a decrease in insulin-like growth factors and their receptors leading to apoptosis of neurons [113][114].…”
Section: Cyclo-oxygenase Pathwaymentioning
confidence: 99%
“…Long-term diabetes has been shown to cause a decrease in insulin-like growth factors and their receptors leading to apoptosis of neurons [113][114].…”
Section: Cyclo-oxygenase Pathwaymentioning
confidence: 99%
“…For example, patients with type 1 diabetes (T1D) are frequently found to have decreased psychomotor speed, mental flexibility, and IQ scores[ 8 , 11 - 13 ]. T1D patients also often show reductions in the volume of regional gray matter in areas such as the prefrontal cortex, hippocampus, and thalamus[ 12 , 14 , 15 ]. On the other hand, affected skills in type 2 diabetes (T2D) are largely executive function, memory, and information processing[ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus in human and rodents brain plays a crucial role in memory/learning and processing information about spatial locations (Burgess et al, 2002). The results from the majority of experimental studies also indicate that diabetes negatively impacts hippocampal cell proliferation and survival (Ho et al, 2013; Chen et al, 2012; Foghi and Ahmadpour, 2013; Li et al, 2002a,b; Jafari Anarkooli et al, 2008). On the other hands, some of experimental studies revealed a reduction in the numerical densities of neurons in some portions of fetal CNS, especially in the hippocampus due to maternal diabetes which reflects in lower memory and learning skills and defect in memory storage (Ghafari et al, 2015; Razi et al, 2014; Golalipour et al, 2012; Khaksar et al, 2011; Tehranipour and Khakzad, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical literature consistently report that the hippocampal environment of hyperglycemic animals favors apoptosis, as evidenced by significant elevations in apoptotic markers (Chen et al, 2012; Foghi and Ahmadpour, 2013; Li et al, 2002a,b; Revsin et al, 2005). There are also several in vitro and in vivo studies indicating that hippocampal apoptotic neuronal loss occurs in diabetic encephalopathy in animals and that this may be a major contributing mechanism to memory and learning impairments (Foghi and Ahmadpour, 2013; Li et al, 2002a; Jafari Anarkooli et al, 2008; Sima et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation